The Permanence and Extinction of a Discrete Predator-Prey System with Time Delay and Feedback Controls - Li Qiuying (Advances in Difference Equations, 2010)
A discrete predator-prey system with time delay and feedback controls is studied. Sufficient conditions which guarantee the predator and the prey to be permanent are obtained. Moreover, under some suitable conditions, we show that the predator species y will be driven to extinction. The results indicate that one can choose suitable controls to make the species coexistence in a long term.